DELIVERY ROUTE OF CHAMOMILE ON THE GROWTH AND SUBSEQUENT PHYSIOLOGY OF BROILER CHICKENS UNDER E. COLI CHALLENGE - & Beski, khishtan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This experiment was conducted to investigate the effect of different levels (5g/kg ,10 g/kg or litter) of chamomile flower in feed and water on performance and gut health of broiler chickens under E. coli challenge. A total of 480-day-old Ross 308 broilers were randomly assigned to 12 treatments each replicated 4 times with 10 birds. Oral inoculation with E. coli was on days 8 and 9 of birds age. At day 10 and 35, the interaction (p